Implementation of Discovery Learning to Improve Scientific and Cognitive Attitude of Students - Erman Syarif; Syamsunardi Syamsunardi; Alief Saputro (Universitas Negeri Makassar, 2020)
This study aims to determine the implementation of discovery learning in improving scientific and cognitive attitudes of students. This type of research is a classroom action research conducted in class X Is7. Each cycle consists of four stages, namely planning, implementing, observing, and reflecting. The instruments in this study were observation sheets, scientific attitude questionnaires and cognitive tests. The results showed: 1) the scientific attitude of the first cycle students showed an average value of 3.9 in either category. Cycle II scientific attitudes of students showed an average value of 4.4 in either category. 2) the average cognitive value in the first cycle with a value of 70.18 in the sufficient category and an increase in the second cycle with a value of 89.23 in the very high category. This improvement illustrates that students have an effort in mastering subject matter. Discovery learning has a positive impact in improving students 'scientific and cognitive attitudes which are marked by an increase in students' learning completeness in each cycle.